C/EBP and nuclear factor of activated T cells differentially regulate Adamts-1 induction by stimuli associated with vascular remodeling - Oller, Jorge; Alfranca, Arantzazu; Méndez Barbero, Nerea; Villahoz, Silvia; Lozano Vidal, Noelia; Martín Alonso, Mara; Arroyo, Alicia G.; Escolano, Amelia; Armesilla, Angel Luis; Campanero, Miguel R; Redondo, Juan Miguel (My University, 2015)
Emerging evidence indicates that the metalloproteinase Adamts-1 plays a significant role in the pathophysiology of vessel re modeling, but little is known about the signaling pathways that control Adamts-1 expression. We show that vascular endothelial growth factor (VEGF), angiotensin-II, interleukin-1 , and tumor necrosis factor , stimuli implicated in pathological vascular remodeling, increase Adamts-1 expression in endothelial and vascular smooth muscle cells. Analysis of the intracellular signal ing pathways implicated in this process revealed that VEGF and angiotensin-II upregulate Adamts-1 expression via activation of differential signaling pathways that ultimately promote functional binding of the NFAT or C/EBP transcription factors, re spectively, to the Adamts-1 promoter. Infusion of mice with angiotensin-II triggered phosphorylation and nuclear translocation of C/EBP proteins in aortic cells concomitantly with an increase in the expression of Adamts-1, further underscoring the im portance of C/EBP signaling in angiotensin-II-induced upregulation of Adamts-1. Similarly, VEGF promoted NFAT activation and subsequent Adamts-1 induction in aortic wall in a calcineurin-dependent manner. Our results demonstrate that Adamts-1 upregulation by inducers of pathological vascular remodeling is mediated by specific signal transduction pathways involving NFAT or C/EBP transcription factors. Targeting of these pathways may prove useful in the treatment of vascular disease.